2018
DOI: 10.1016/j.adaj.2018.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Controlling caries in exposed root surfaces with silver diamine fluoride

Abstract: Yearly 38% SDF applications to exposed root surfaces of older adults are a simple, inexpensive, and effective way of preventing caries initiation and progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 21 publications
5
59
0
7
Order By: Relevance
“…To our knowledge, it is the rst study to examine population-level SDF survival in a real-world context characterized by in situ treatment decision-making, the rst study to examine SDF outcomes using dental claims data, and one of the few studies to examine SDF survival among older children, adolescents, working-age adults, and patients prioritized in community dental outreach other than school-based settings. Overall, our ndings support previous conclusions that SDF is an effective treatment that arrests caries [6,[10][11][12][13][14][15][16][17]. Importantly, our study nds also merit in using SDF to prevent early carious lesions, thus contributing meaningful evidence to the knowledge gap that underlies national guidelines in which SDF is only recommended for treating extant disease [8,9].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…To our knowledge, it is the rst study to examine population-level SDF survival in a real-world context characterized by in situ treatment decision-making, the rst study to examine SDF outcomes using dental claims data, and one of the few studies to examine SDF survival among older children, adolescents, working-age adults, and patients prioritized in community dental outreach other than school-based settings. Overall, our ndings support previous conclusions that SDF is an effective treatment that arrests caries [6,[10][11][12][13][14][15][16][17]. Importantly, our study nds also merit in using SDF to prevent early carious lesions, thus contributing meaningful evidence to the knowledge gap that underlies national guidelines in which SDF is only recommended for treating extant disease [8,9].…”
Section: Discussionsupporting
confidence: 86%
“…The existing literature on SDF focuses primarily on young children who still have primary dentition [10,13,15,[22][23][24][25][26][27][28] and older adults [16,30], often omitting older children, adolescents, and working-age adults. The strongest evidence on SDF derives from randomized controlled trials (RCTs) whether individual or aggregated into evidence reviews, which compare SDF with placebo or other treatments, limit the intervention to SDF alone versus when used in combination with restorative procedures, and generate ndings from samples treated under ideal clinical conditions and from analyses that control for covariates [6,[10][11][12][13][14][15][16][17]. While this evidence supports SDF effectiveness in arresting caries lesion development and progression, accounts or analyses of "real world" concerns such as the settings in which treatments are delivered, patient volume at scale, and clinical decision-making when multiple treatment options are available, are limited in literature, as is evidence of the potential for SDF to prevent caries This study aims to address some of these limitations, with particular concern for dentally underserved patients who obtain care in community settings, who are also historically excluded from clinical trials due to geographic and other barriers.…”
mentioning
confidence: 99%
“…Fortunately, dentists have a range of preventive and restorative products that can be used for the most aggressive caries progression, such as high‐fluoride toothpastes, silver diamine fluoride, and glass‐ionomer cements . If used early in disease progression, high‐fluoride toothpastes can help prevent caries; and if used in the more advanced stages, it can help slow ROHD progression .…”
Section: Promoting Oral Health Care For Patients With Alzheimermentioning
confidence: 99%
“…Three randomized controlled trials were included, and the preventive fraction for SDF was found to be 71% when compared against a placebo in a 3-year study and 25% in a 2-year study. 228,229 SDF was found to be as effective as either chlorhexidine or sodium fluoride varnish in preventing new root caries, and it showed much higher caries arrest than the placebo control. No serious adverse effects were reported in any of the 3 studies, and few complaints about black staining were noted.…”
Section: Silver Diamine Fluoridementioning
confidence: 93%